VARIABEL YANG MEMPENGARUHI KRIMINALITAS DI WILAYAH SULAWESI UTARA MENGGUNAKAN REGRESI DATA PANEL - Rahmasari, Dwi Hartiana; Yulianto, Safaat (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2025)
North Sulawesi Province has high economic and tourism potential due to its rich agricultural and mining resources and natural beauty, attracting investors and tourists. However, the high crime rate in North Sulawesi Province raises concerns about economic sustainability and social stability. Investors will tend to choose safe and stable places to invest, while tourists will also choose safe places to vacation. This study aims to analyze the variables that influence crime rates in North Sulawesi Province. Previous studies have shown that crime rates are influenced by several factors, including education, unemployment, poverty, and inequality. These variables will be analyzed using panel data regression. Panel data regression is used because crime rates vary across regions and over time. Thus, panel data can reveal the effects of inter-regional and inter-temporal factors. The study covers 11 districts and 4 cities in North Sulawesi Province, spanning the period from 2021 to 2023. The results of the panel data regression indicate that the most appropriate model is the Fixed Effect Model (FEM). Based on the results of the Fixed Effect Model (FEM), it is found that poverty and inequality significantly influence crime, while education and unemployment do not significantly influence crime. The Adjusted R Square value is 0.8132, meaning that 81.32% of crime in the North Sulawesi region can be explained by education, unemployment, poverty, and inequality, while 18.68% is explained by other factors.